2004
DOI: 10.1007/s00392-004-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Class-specific pro-apoptotic effect of statins on human vascular endothelial cells

Abstract: Neonangiogenesis represents an important step in tumor development and propagation. Statins may have anticancerogenic potential by blocking vascular endothelial cell growth. The antiproliferative effect of four statins on human endothelial cells was compared, concomitantly delineating a possible pro-apoptotic process. All four statins tested, i. e. atorvastatin, fluvastatin, lovastatin, and simvastatin inhibited cell proliferation. Nearly complete blocking of cell proliferation was achieved at a concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Several studies have suggested that the anti-angiogenic activity of statins is achieved by inhibiting proliferation and migration of endothelial cells, as well as inducing cell apoptosis (Negre-Aminou et al , 1997; Pirillo et al , 1997; Sato et al , 1998; Kaneta et al , 2003; Muck et al , 2004; Schaefer et al , 2004); however, these studies used high concentrations of statins ranging from 2 to 100  μ M in vitro . To reach serum concentrations of 2–20  μ M , simvastatin has to be administered at a daily dose of 100–200 mg kg −1 , a dose not feasible for human use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested that the anti-angiogenic activity of statins is achieved by inhibiting proliferation and migration of endothelial cells, as well as inducing cell apoptosis (Negre-Aminou et al , 1997; Pirillo et al , 1997; Sato et al , 1998; Kaneta et al , 2003; Muck et al , 2004; Schaefer et al , 2004); however, these studies used high concentrations of statins ranging from 2 to 100  μ M in vitro . To reach serum concentrations of 2–20  μ M , simvastatin has to be administered at a daily dose of 100–200 mg kg −1 , a dose not feasible for human use.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, at high micromolar concentrations, they have anti-angiogenic activity and may be of special significance for cancer therapy. The anticancer effects of statins have been shown to result from the inhibition of endothelial cell proliferation and migration, as well as the induction of apoptosis (Negre-Aminou et al , 1997; Pirillo et al , 1997; Sato et al , 1998; Kaneta et al , 2003; Muck et al , 2004; Schaefer et al , 2004); however, a limitation in using statins for cancer therapy is that the required doses are too high to be applied to patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 28 , 29 Statins may also have a direct antimicrobial effect, 30 and possible antibacterial activity of statins against a variety of pathogens may be attributed to their ability to suppress cell growth, and to promote apoptosis. 31 33 …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that reduced apoptosis contributes to the synovial inflammatory process [12]. In vitro statins were shown to exert a cytotoxic effect on human T, B and myeloma cells by promoting their apoptosis [14] and also modifying apoptosis of smooth muscle and endothelial cells leading to altered vascular function and neovascularisation [15]. …”
Section: Introductionmentioning
confidence: 99%